2019
DOI: 10.1002/jum.15185
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation Effects and Mechanisms of Low‐intensity Focused Ultrasound on Pain Triggered by Soft Tissue Injury

Abstract: Objectives-Pain caused by soft tissue injury (STI) is always intractable and will eventually result in physical and psychological problems. This experiment aimed to assess the efficacy and mechanisms of low-intensity focused ultrasound (LIFU) for pain-related STI.Methods-Rabbits (n = 30) with STI were given fixed treatment for 20 seconds and then mobile treatment for 60 seconds daily for 10 consecutive days by an LIFU device with a power output of 5 to 6 W and a frequency of 0.8 MHz. To evaluate the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Recent investigations on the interactions between sound pressure waves and brain tissue suggest that ultrasound primarily exerts its modulatory effects through mechanical action on cell membranes, notably affecting ion channel gating ( Kubanek et al, 2016 ). Liang et al (2020) explored the efficacy and mechanisms of tFUS in treating pain caused by soft tissue injury. Low-intensity focused ultrasound relieved pain, and the mechanism could be attributed to decreasing the release of analgesic substances from the nerve and reducing local inflammatory factors ( Liang et al, 2020 ).…”
Section: Evidence For Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations on the interactions between sound pressure waves and brain tissue suggest that ultrasound primarily exerts its modulatory effects through mechanical action on cell membranes, notably affecting ion channel gating ( Kubanek et al, 2016 ). Liang et al (2020) explored the efficacy and mechanisms of tFUS in treating pain caused by soft tissue injury. Low-intensity focused ultrasound relieved pain, and the mechanism could be attributed to decreasing the release of analgesic substances from the nerve and reducing local inflammatory factors ( Liang et al, 2020 ).…”
Section: Evidence For Mechanismsmentioning
confidence: 99%
“… Liang et al (2020) explored the efficacy and mechanisms of tFUS in treating pain caused by soft tissue injury. Low-intensity focused ultrasound relieved pain, and the mechanism could be attributed to decreasing the release of analgesic substances from the nerve and reducing local inflammatory factors ( Liang et al, 2020 ). Na Pang et al (2021) demonstrated that transcranial ultrasound stimulation was effective in modulating the learning behaviors of mice and the expression of apoptosis, oxidative stress, and inflammation.…”
Section: Evidence For Mechanismsmentioning
confidence: 99%
“…17 Previous studies have confirmed that LIFU has a significant pain relief effect on soft tissue injuries. 17 Therefore, we believe LIFU has potential application value in relieving DOMS after high-intensity exercise.…”
mentioning
confidence: 92%
“…However, the clinical efficacy of traditional ultrasound treatment has not been well proved, which may be due to insufficient ultrasound dose in the injured area 16 . Low‐intensity focused ultrasound (LIFU) was designed to focus the ultrasonic beams on the target area without damaging the acoustic channels 17 . Previous studies have confirmed that LIFU has a significant pain relief effect on soft tissue injuries 17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation